Reliability and validity of the Chinese version of the PedsQL Multidimensional Fatigue Scale in children with acute leukemia - Qimeng Ye; Ke Liu; Jun Wang; Xiuqing Bu; Lili Zhao (Elsevier, 2016)
Background: The PedsQL Multidimensional Fatigue Scale (PedsQL™ MFS) is widely used to rate fatigue in children living in English-speaking countries. However, insufficient instruments are available to conduct parallel assessment on fatigue in parents and children in China. In this regard, an appropriate measurement method must be developed. Objectives: This study aims to determine the reliability and validity of the Chinese-language PedsQL™ MFS. Methods: Children with cancer (n = 125) and their parents were surveyed in Guangzhou, China. The parents of children aged 2-4 years completed the PedsQL™ MFS proxy reports, whereas the other children and their parents completed the questionnaires by themselves. Results: The PedsQL™ MFS-Chinese version demonstrated satisfactory internal consistency reliability (child self-report Cronbach's α = 0.87; parent self-report Cronbach's α = 0.93). The factor loadings of the items ranged from 0.78 to 0.87 for general fatigue, 0.56-0.78 for sleep/rest fatigue, and 0.62-0.89 for cognitive fatigue. Conclusion: This study proves that the PedsQL™ MFS-Chinese version is an effective tool for screening fatigue in Chinese children with cancer.